Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445682
|View full text |Cite
|
Sign up to set email alerts
|

What We Can Learn From Visual Artists About Software Development

Abstract: This paper explores software's role in visual art production by examining how artists use and develop software. We conducted interviews with professional artists who were collaborating with software developers, learning software development, and building and maintaining software. We found artists were motivated to learn software development for intellectual growth and access to technical communities. Artists valued efficient workflows through skilled manual execution and personal software development, but avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…• Artistic disciplines: Through the exchange of knowledge and current learning practices in the artistic disciplines outside of engineering design, such as visual arts, architecture, interior design, and sculpture making, we aim to inspire new ways of supporting learning creative skills through iteration and prototyping [10,21,26]. By connecting to these other disciplines inherent in fabrication, but often neglected, we will explore how this integration expands the ways learners can create and participate within educational fabrication experiences.…”
Section: Topics For Discussionmentioning
confidence: 99%
“…• Artistic disciplines: Through the exchange of knowledge and current learning practices in the artistic disciplines outside of engineering design, such as visual arts, architecture, interior design, and sculpture making, we aim to inspire new ways of supporting learning creative skills through iteration and prototyping [10,21,26]. By connecting to these other disciplines inherent in fabrication, but often neglected, we will explore how this integration expands the ways learners can create and participate within educational fabrication experiences.…”
Section: Topics For Discussionmentioning
confidence: 99%
“…p5.js (or p5 for short) uses the metaphor of a sketchbook, attempting to make drawing with code as intuitive as drawing with paper and pen. Previous research has argued for pairing art production with tool production to foster broader participation in creative system development [23]. p5 has over 1.5 million users, known also as creative coders [22].…”
Section: Programmatic Direct Control Of 3d Printersmentioning
confidence: 99%
“…Issuing commands straight to the printer helped them discern "the direct result of tweaking things like speed and extrusion". Li et al [23] found that in digital art tools, automation often added tedious manual labor instead of reducing it because artists lacked control over outcomes. Our formative study and workshops indicate a similar concern over lack of control in the toolpath planning process.…”
Section: Tools To Support Materials Practicementioning
confidence: 99%
“…Andrés has recently worked on and published about AR in an industrial research lab, including most recently on AR activism [112]. Jennifer has discussed the efects of AR on self-image perception [55] and is interested in informing HCI research from the knowledge of professionals and feld experts [75].…”
Section: Researcher Positionality Statement and Backgroundsmentioning
confidence: 99%